2007
DOI: 10.1038/sj.ejcn.1602954
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of red or processed meat does not predict risk factors for coronary heart disease; results from a cohort of British adults in 1989 and 1999

Abstract: Objectives: To investigate whether a high consumption of red or processed meat is associated with increased risk of coronary heart disease (CHD). Subjects/Methods: The subjects were 517 men and 635 women, who were members of the Medical Research Council National Survey of Health and Development, 1946 birth cohort. Assessment of diet was carried out at two time points 1989 and 1999 with outcome measures collected in 1999. Food intake data were recorded in 5-day diaries. Meat consumption was estimated by adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…In fact, based on moderate evidence, the 2010 U.S. Dietary Guidelines Advisory Committee recently concluded that there is "no clear association between intake of animal protein products and blood pressure in prospective cohort studies." A prospective study by Wagemakers, Prynne, Stephen, and Wadsworth (2009), using data from the National Survey of Health and Development in England, found no association between red (beef, lamb, pork, veal and mutton) or processed meat (ham, bacon, sausages, processed meat cuts, and processed minced meat) and blood pressure but the combination of the two was associated with higher blood pressure in men. Likewise, Pitsavos et al (2006) failed to show a positive relationship between red meat intake and increased blood pressure in a cross-sectional study conducted in Greece with self-reported diagnosis of hypertension higher among people reporting fewer servings of total red meat and pork per week.…”
Section: Red Meat and Cardiovascular Healthmentioning
confidence: 98%
“…In fact, based on moderate evidence, the 2010 U.S. Dietary Guidelines Advisory Committee recently concluded that there is "no clear association between intake of animal protein products and blood pressure in prospective cohort studies." A prospective study by Wagemakers, Prynne, Stephen, and Wadsworth (2009), using data from the National Survey of Health and Development in England, found no association between red (beef, lamb, pork, veal and mutton) or processed meat (ham, bacon, sausages, processed meat cuts, and processed minced meat) and blood pressure but the combination of the two was associated with higher blood pressure in men. Likewise, Pitsavos et al (2006) failed to show a positive relationship between red meat intake and increased blood pressure in a cross-sectional study conducted in Greece with self-reported diagnosis of hypertension higher among people reporting fewer servings of total red meat and pork per week.…”
Section: Red Meat and Cardiovascular Healthmentioning
confidence: 98%
“…In general, plant proteins have been related to health benefits more than animal proteins (14)(15)(16)(17) . While vegetable protein intakes have been found to be inversely associated with blood pressure (18) , a high consumption of red and/or processed meat has been associated with a number of adverse cardiovascular health outcomes such as higher systolic blood pressure (19) , increased risk for type 2 diabetes (20)(21)(22) , ischaemic stroke (23) , global and central obesity (24,25) and weight gain (26,27) .…”
mentioning
confidence: 99%
“…Interestingly, a recent study including 1152 subjects (635 women and 517 men) failed to find a significant association between red or processed meat intake and serum cholesterol level or blood pressure (Wagemakers, Prynne, Stephen, & Wadsworth, 2009). A very modest association could only be observed between red or processed meat intake and waist circumference in men (p = 0.04) but not in women (p N 0.05).…”
Section: Discussionmentioning
confidence: 75%